2020
DOI: 10.1177/2325967120913020
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Incidence and Impact on Player Performance in Major League Baseball Players Before and After a Standardized Concussion Protocol

Abstract: Background: Sports-related concussions have garnered significant attention in recent years because of the negative effects they can have on a player’s cognitive health and performance. In response to this growing concern, Major League Baseball (MLB) introduced a standardized concussion protocol during the 2011-2012 season. Purpose/Hypothesis: The purpose of this study was to compare the reported incidence of concussions and the subsequent performance of MLB players before and after the introduction of the stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…It should be noted that concussion incidence did not change throughout the reporting period. Baseball concussion incidence has been minimal in previous literature 5 , 38 , despite a concussion protocol instituted in the 2011–2012 season 39 .…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that concussion incidence did not change throughout the reporting period. Baseball concussion incidence has been minimal in previous literature 5 , 38 , despite a concussion protocol instituted in the 2011–2012 season 39 .…”
Section: Discussionmentioning
confidence: 98%
“…There was no evidence found surrounding the incidence of post‐concussion syndrome following cricket‐related head injuries, or the impact of concussion on subsequent cricket performance in the short or long term. However, a recent study in the analogous field of baseball demonstrated significant detriment to batting performance 1 year following concussion, that persisted through the remainder of their careers 76 . Though this is a finding that contrasted to preceding studies, 77 this potential impact of concussion on subsequent performance is an important consideration in relation to cricket injuries and represents an important question for future cricket‐related research.…”
Section: Long‐term Sequelae Of Concussionmentioning
confidence: 95%
“…Assessment Tool, version 5 (SCAT5). In 2011, the MLB introduced a standard concussion protocol requiring (1) preseason neurocognitive baseline testing (SCAT5), (2) use of SCAT5 as a standardized concussion screening tool during play, (3) mandatory 7-day disabled list (DL) for concussed players, (4) return to baseline neurocognitive function before return to play, and ( 5) prohibition of same-day return to play [38,39]. The incidence of reported concussions significantly increased after implementation of the new protocol in alignment with the improved awareness of concussion presentation and symptoms throughout sports medicine.…”
Section: Common Neurological Tests Used For Concussion Diagnosis Incl...mentioning
confidence: 99%
“…The incidence of reported concussions significantly increased after implementation of the new protocol in alignment with the improved awareness of concussion presentation and symptoms throughout sports medicine. The increased reporting incidence may also be partially attributed to shortening the mandatory DL from 15 to 7 days, thus mitigating fear of losing a spot on the roster and encouraging players to disclose symptoms [39,40].…”
Section: Common Neurological Tests Used For Concussion Diagnosis Incl...mentioning
confidence: 99%